Extendable intramedullary nailing in a child with osteogenesis imperfecta of bilateral femoral fractures: a case report - Zhang, Weishuai; Lu, Xuchao; Yang, Nannan; Zhu, Xianyou; Hu, Haotian (Frontiers in Surgery, 2026)
BackgroundOsteogenesis imperfecta, commonly referred to as brittle bone disease, is the most prevalent monogenic bone disorder and is characterized by osteoporosis and heightened bone fragility. Most patients experience multiple fractures, some of which can be managed conservatively; however, patients with numerous fractures frequently develop significant limb deformities and growth abnormalities that require surgical intervention. For adult patients, intramedullary fixation of osteotomies is typically the preferred option; however, this approach is less suitable for children due to their ongoing growth and development, which necessitates periodic replacement of intramedullary nails and thus repeated surgeries. Moreover, increased bone fragility and a high propensity for fractures in children with osteogenesis imperfecta contribute to frequent postoperative complications, such as refractures and displacement of internal fixation. To address these challenges, extendable intramedullary nails have been developed. In this context, we used these nails to treat a pediatric patient with multiple femoral fractures and severe deformity, with favorable clinical outcomes during a 2-year postoperative follow-up.Case reportWe present the case of a 12-year-old female patient with postnatally diagnosed osteogenesis imperfecta who sustained multiple fractures over time, the most severe being bilateral femoral fractures. She was admitted to our facility on two occasions for femoral shaft fractures. We employed osteotomy, orthopedic techniques, and extendable intramedullary nailing for her treatment. Postoperatively, she showed satisfactory recovery from bilateral femoral deformities, with successful fracture healing and near-normal lower limb lengths.ConclusionExtendable intramedullary nailing exhibits favorable clinical efficacy in the management of fracture-related deformities in pediatric patients with osteogenesis imperfecta, offering novel insights and options for clinical diagnosis and treatment, thereby demonstrating significant clinical utility.